The Application of Communal Mating and Introduction of Rex Rabbit Bucks to Community Rabbit Breeder in Kulonprogo, Yogyakarta - Rahmat Bintang Ramadhan; Bunga Putri Sepwiati; Monica Caroluna Naidilah Dwi Putri; Widya Nur Amalia; Zaenab Nurul Jannah; Adi Tiya Warman; Amir Husaini Karim Amrullah; Bayu Andri Atmoko; Panjono Panjono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The rabbit farming business has great potential to meet the need for animal protein, and currently, many rabbit farming businesses are being cultivated. Farmers face nonoptimal reproductive performance with the currently implemented mating management, so improvement efforts are needed. The community service aimed to implement good breeding practices through communal mating and introducing bucks Rex rabbits to rabbit breeders in Kulonprogo, Yogyakarta. The community service activities were conducted from June to September 2023 at one of the rabbit breeders in Kulonprogo Regency, Yogyakarta. The activities include: 1. initial preparation and coordination, 2. preparation of extension materials, guidebooks (assistance media), 3. Direct training through extension. 4. Implement communal mating, introduce Bucks Rex directly at partner locations, and distribute guidebooks. 5. Monitoring and evaluation of activity results. The enthusiasm of breeders in community service was proven by the presence of 30 breeders in extension and discussion activities with the theme